NEUROMODULATION FOR OVERACTIVE BLADDER WITH TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION IN ADULTS – A RANDOMIZED CLINICAL STUDY - LOUREMBAM SURBALA; P. RATAN KHUMAN; VASVELIYA MITAL; BHATT DEVANSHI (International Journal of Pharma and Bio Sciences, 2014)
Neuromodulation has become a well-established treatment modality in OAB. Neuromodulation with Transcutaneous Electrical Nerve Stimulation (TENS) at sacral foramina (SF), Posterior tibial nerve (PTN) and combination of SF+PTN stimulation was being compared in a randomized assessor blinded prospective clinical study. 44 adult participants with OAB were randomly distributed into three groups (SF, PTN: n = 15 each and SF+PTN: n = 14). TENS was given daily for 20 minutes using standardized parameter for 4 weeks. An OAB Symptom Score (OABSS), Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7) were recorded at baseline and at the end of 4 weeks of intervention. The results of the study show that all neuromodulation methods were significantly effective (p<0.05) in reducing symptoms of OAB. It was found that simultaneous stimulation at SF+PTN proves to be the most effective method compared to stimulation at SF and PTN alone. The study concluded that TENS is safe and acceptable with potential clinical effects in reducing symptoms of OAB in adult participants.